The Effect of Socio a Economic Survival of Okada Riders on African Cultural Values (Global Journal of Human-Social Science, 2012)
This study investigated effects of socio economic survival of Okada riders in Abeokuta and Odeda Local Government Areas of Ogun State Nigeria on African cultural values The study was carried out using the questionnaire method to elicit vital information from one hundred respondents who were randomly- selected from ten Okada parks within Abeokuta metropolis and Odeda township respectively Simple percentage and t-test statistical tools were used to analyse the data The findings showed that Okada riding though a lucrative enterprise has its direct and indirect bearing on the cultural values of the society The recklessness that is associated with the business tends to erode certain cultural and moral values including respect for other road users respect for authority and elders within the immediate environment Majority of the riders engaged in the business because of the pressing need to survive and sustain their families Furthermore most of the riders did not take the necessary safety precautions they used foul languages and drank alcohol even during business hours and these reasons have been identified as major causes for their recklessness In Conclusion Okada business is lucrative and can add to the Nigerian economy rather than constituting a menace Riders should be given adequate training on societal ethics Citizenship education should also form part of the training to be conducted for those intending to get into the trade They should be encouraged to register properly at zonal and state levels Moreover the Federal State and Local governments authorities should set up regulatory bodies empowered to monitor their activities and mode of operations
Keywords: okada riders; socio – economic survival; African cultural values